PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PERTANYAAN YANG DITANAM UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS VI.C SD NEGERI 024 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Sumarni Elda (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low activeness student learning in science classes subjects class VI.C SD Negeri 024 Tarai Bangun. This study aims to determine the increase activeness student in classroom lesson IPA class VI.C SD Negeri 024 Tarai Bangun through application of cooperative learning model planted question, which was conducted over 1 month. The subjects were class VI.c SD Negeri 024 Tarai Bangun by the number of students as many as 27 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research, the conclusion to this study is based on the analysis and discussion in chapter IV can be inferred through cooperative learning model can improve the planted questions that activeness students in science subjects at Grade VI.C 024 SD Negeri 024 Tarai Bangun, evidenced by the increase in the activity of the students from the first cycle to the second cycle. On the preliminary data obtained average value of 42.6% of the first cycle of the first meeting students' learning activeness is low with an average of 50.9% and in the second meeting of the liveliness of the students classified as moderate with an average of 58.3%. While the activity of students in the second cycle the first meeting there was an increase by an average of 66.7% with a high category and the second meeting obtain figures, the average percentage of 80.6 with the category of very high category.